Soybean yield as a consequence of harvest delay and environmental conditions - Tsukahara, Rodrigo Yoiti; Fonseca, Inês Cristina de Batista; e Silva, Marcelo Augusto de Aguiar; Kochinski, Edson Giovanni; Prestes Neto, José; Suyama, Juliana Tamie (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of harvest delay on grain moisture, thousand grain weight, and soybean productivity, as well as to identify the most important meteorological variables during pre‑harvest and to propose empirical algorithms to estimate soybean yield losses. The experiments were carried out in the municipalities of Castro, in the state of Paraná, and of Itaberá, in the state of São Paulo, Brazil, in the seasons from 2011/2012 to 2013/2014, with the soybean cultivar 'NA5909RG', in seven environments. Treatments consisted of eight harvest times of soybean after phenological stage R8.2. The analysis of group of experiments showed a significant interaction between environments and harvest times. Grain moisture and grain yield are directly affected by the number of days with rainfall equal to or higher than 3 mm. At the R8.2 phenological stage, the highest values of productivity are obtained; however, after this stage, there is a decline of productivity as a consequence of harvest delay. The greatest, accumulated losses of productivity occur in environments with high frequency of rainfall, and high temperature and solar radiation. Two algorithms based on agrometeorological variables are proposed to estimate soybean yield loss.